d EFFECT OF CYLINDRICAL PIN DEPTH ON THE TEMPERATURE DISTRIBUTION OF DISSIMILAR FRICTION STIR SPOT WELDING (FSSW): abstract, introduction, mathematical and experimental models, results and discussion, conclusions (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2019)
Friction stir spot welding (FSSW) is provided a premium difference to resistance spot welding and rivet process for making the structures of aluminum sheet and it is a new development. ANSYS works is done which conducted on dissimilar material sheets of a1.1mm thick sheet of aluminum alloy (AA2024-T3) and a 0.8mm thick sheet of carbon steel (1006-AISI). A 3-D finite element model was built using ANSYS APDL to simulate the thermal and mechanical model during FSSW. The welding processes are performed using cylindrical pin with a 10mm diameter. Three tool rotational speeds are used during FSSW processes (900rpm, 1400rpm, 1800rpm). Results showed that the maximum temperature was 242.57ºC in nugget zone of dissimilar spot weld, at 15sec with a 0.4mm depth and 135.752°C at 10sec with a depth of 0.2mm.